The reading practice in the School Group Barão de Mipibu in the 1940s (Research, Society and Development, 2017)
The school has been important in the reader’s development, because it is considered as a privileged institution of valorization, formation and consolidation of reading. The first half of 20th century in Brazil was marked by the dissemination of primary schools through school groups, institutions that presented itselves as ways of literacy of brazilian children, in other words, of inclusion in the letters world. However, we noticed that are still a few papers that includes researches about the reading practice in those educational institutions, within the context of History of Reading. Therefore, the present article aims to approach this reading of the thematic through the reading practice study in the School Group Barão de Mipibu during the 1940 decade, period when we noticed a further development in the literary production, including in the textbooks, through the growth of publishers in Brazil, but which contrasted with the high illiteracy rate in the country. We aim to analyze which kind of readings was offered to the students by the institution, the books that appeared the most in the lists and therefore to understand the purpose of the books using found in the school library, as well as to perceive the circulation of the material, revealing the relation between students and reading. To perform this research, we used as sources: the relation of movable and the borrowing registers of the School Group Barão de Mipibu books. We chose to develop the paper through the view of Cultural History and to contribute to the theoretical basis we seek to dialogue with authors who cover the subject, namely: CHARTIER (2003); DARNTON (2011), CASTRO (2015) e VIDAL (2001).  Through the research we could determine that the reading practice was fragile and presented many challenges in its consolidation and that even in front of teaching reforms of the period and the increase in the books production, the reading habit was not an unusual practice among the School Group Barão de Mipibu students.